1929
DOI: 10.1177/003591572902201008
|View full text |Cite
|
Sign up to set email alerts
|

Gastro-Intestinal Focal Infection in Relation to Oral Sepsis, with Special Reference to Anaerobes, Occurring in Six Cases of Mental Disorder

Abstract: Gastro-intestinal Focal Infection in Relation to Oral Sepsis, with special reference to Anaerobes, occurring in Six Cases of Mental Disorder. By W. M. FORD ROBERTSON, M.B., Ch.B. ON the subject of focal infection in relation to mental disorders much work has

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1929
1929
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Ford Robertson reported that 54% of patients (vs. 20% of healthy controls) were outside of normal gastric acid production, the majority being in a state of hypochlorhydria. Robertson concluded that the loss of the bactericidal effects of normal gastric acidity could have far reaching effects in mental health, including neurasthenia and in those “borderland patients” that otherwise presented with sub-threshold symptoms [81]. In 1912 Francis Brook, a physician at Guy’s Hospital in London, began to examine the fecal microflora of neurasthenic patients, reporting significant differences in about half of 132 patients encountered.…”
Section: Series Introductionmentioning
confidence: 99%
“…Ford Robertson reported that 54% of patients (vs. 20% of healthy controls) were outside of normal gastric acid production, the majority being in a state of hypochlorhydria. Robertson concluded that the loss of the bactericidal effects of normal gastric acidity could have far reaching effects in mental health, including neurasthenia and in those “borderland patients” that otherwise presented with sub-threshold symptoms [81]. In 1912 Francis Brook, a physician at Guy’s Hospital in London, began to examine the fecal microflora of neurasthenic patients, reporting significant differences in about half of 132 patients encountered.…”
Section: Series Introductionmentioning
confidence: 99%